Les pressions écologiques réglementaires : comment les entreprises tunisiennes les gèrent-elles ? - Ahmed Turki (Développement Durable et Territoires)
Companies are today more and more called to consider the ecological aspects in their management. They are the target of the ecological pressures the main source of which is public authorities. So, the present paper suggests studying the nature of the relation between companies and public authorities in environmental protection. To reach this objective, a case study is made on 8 Tunisian companies among which two are certified to the standard ISO 14001. The results show that public authorities (constitute) the most and sometimes the only source of ecological pressure in the Tunisian context. These pressures show themselves by overhauls and penalties. These companies find that the environmental legislative standards are difficult to achieve. So, the results identify two types of relation between companies and public authorities: cooperative and conflicting. Also, the case study shows that the ecological pressures decreased further to the ecological initiatives.